Caracterização fenotípica e identificação molecular de bactérias multirresistentes em efluente não tratado de um hospital no Brasil - Suldofski, Monica Tereza (2021)
In recent decades, bacteria of the Enterobacteriaceae family have acquired an increasingly important role in hospital infections due to their prevalence and high rates of antimicrobial resistance associated with mortality. This resistance due to carbapenemase production is recognized worldwide as a significant emerging problem for hospitalized patients due to the localization of genes in transferable elements, facilitating their spread. This study aimed to characterize phenotypically and genetically carbapenemase-producing Enterobacteriaceae in untreated hospital wastewater. Seasonal collections were performed from summer to spring 2019, considering the absence of rain for its realization. The phenotypic analysis identified 30 strains, from which it was possible to register five species, distributed in eight strains identified throughout the year, that expressed extended-spectrum β-lactamases (ESBLs). Moreover, among the ESBLs registered, four presented a blaKPC resistance profile. Genotypic identification by Polymerase Chain Reaction (PCR) technique detected one strain of K. pneumoniae ssp. pneumoniae isolated in the fall, which showed a positive phenotype for ESBL. The strain of K. pneumoniae ssp. Pneumoniae isolated in the summer sample showed resistance to carbapenems (Meropenem, Ertapenem, and Imipenem), where the blaKPC gene encoded the carbapenemase in addition to producing ESBL. In the fall period, a strain with phenotypic characteristics of Enterobacter cloacae with a resistance profile to Ertapenem, Meropenem, and Imipenem was isolated. In this case, the genotypic profile detected was carbapenemase encoded by the blaKPC gene. In winter, a strain of Klebsiella oxytoca and Escherichia coli were isolated, both resistant to carbapenems encoded by the blaKPC gene. Through this study, we detected the presence of the blaKPC gene among enterobacterial species. In addition, it may be being carried with other resistance determinants, increasing the difficulty in treating the hospital environment. The apparent predominance of some multidrugresistant strains worldwide emphasizes the importance of elucidating the mode of dissemination and epidemiology of multidrug-resistant bacterial isolates in hospitals on a regional, national, and global scale. This study also supports the hypothesis that untreated hospital effluent may act as reservoirs for clinically meaningful multidrug-resistant bacteria, posing a potential risk to human and animal health.